ANALISIS PERAN GANDA PADA PEREMPUAN TERDIDIK DALAM PERSPEKTIF SOSIAL - EKONOMI DAN ETNIS DI INDONESIA - FADHILLAH SHANTIKA ; Prof. Dr. M. Pudjihardjo, SE., MS. Prof. Devanto Shasta Pratomo, SE., M.Si., Ph.D (Thesis Ilmu Ekonomi FEB - UB, 2019)
Education for women has been prioritized to improve their status of women's roles. Educated women in Indonesia often have to choose between the traditional role (domestic sphere) and transitional role (public sphere). Using IFLS5 with a sample of 18,831 respondents, the data were analyzed using binary logistic regression method. This study aims to analyse the influence of trends in social characteristics (age, marital status, higher education level), economic characteristics (dependents of children under 15 years old and family’s economic conditions) and ethnical characteristics in that Indonesian ethnicities that are dominated by educated women in Indonesia (Javanese, Sundanese, Minang, Batak, Balinese, Betawi, and Sasak) on the role of educated women in Indonesia. The results show that women who are in productive age, women with higher education levels, women with dependents of children under 15 years old and women in families with adequate household conditions tend to to choose public sphere. While educated women who are married have a tendency as housewives (domestic spheres). The tendency of women with university education background tend to be 68% higher for work participation. In addition, the results show that educated women from Batak and Balinese have the greatest tendency to enter the labor market (public sphere) of all other ethnicities in Indonesia. Keywords: Educated Woman, Double Burden, Ethnicity, Binary Logistic JEL Classification : J16, J24